Corporate Social Responsibility, its Lights and Shadows. The Case of Iberdrola - Da Costa Pimenta, Clayson Cosme (Journal of the University of Zulia, 2024)
The objective of the article is to critically examine the place of Corporate Social Responsibility (CSR) in the specific case of Iberdrola, an energy company in Spain that has been signified by its formal commitment to the principles of CSR. The main hypothesis is as follows: Iberdrola is an example of greenwashing, using CSR as a marketing tool. The methodology used is qualitative, based on the critical case study method; the information has been collected through a systematic bibliographic review, as well as by comparing the company’s official documentation with the company’s actual practices. The results of the research are as follows: it is found that for Iberdrola is fundamental the set of aspects affecting CSR; of the sustainable development goals (SDGs), Iberdrola partially meets the objectives number 8, 9 and 12; Iberdrola deliberately assumes the interrelation of the three main areas of CSR; there is insufficient horizontal collaboration between certain stakeholders; Finally, there is a partial compliance with the decalogue of principles of the Global Compact for Corporate Social Responsibility. . It is concluded that Iberdrola is a case of partial assumption of the principles of CSR., so it persists true even certain greenwashing.